Leaders’ Individualized Consideration and Employees’ Job Satisfaction - DR. SYED HAIDER KHALIL; SHEHNAZ SAHIBZADAH (Journal of Business & Tourism, 2021)
Individualized Consideration is an important factor affecting organizational employees’ job satisfaction. Many studies show that Individualized Consideration of leadership has positive and significant influence on job satisfaction. Based on a literature review and previous work, this study aims to investigate the influence of Individualized Consideration on organizational job satisfaction. The findings of this study provide evidence that Individualized Consideration have significant positive influence on job satisfaction. The study suggests that if organizations heads demonstrate Individualized Consideration, it will be proven, highly effective to achieve employees’ job satisfaction in their organizations.